2010
DOI: 10.14742/ajet.1083
|View full text |Cite
|
Sign up to set email alerts
|

Grappling with technology: A case of supporting Malaysian Smart School teachers' professional development

Abstract: This paper discusses the challenges faced by a group of Smart School teachers in a partnership model designed to help them develop professionally through the use of online tools. This model known as e-CPDelT: Model 2020 is loosely based on the successful, UK based Improving the Quality of Education For All (IQEA) project (Hopkins et al., 1996). The model was piloted on 20 teachers of English, mathematics and science from 5 Smart Schools around Kuala Lumpur. It features collaboration between these teachers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…TAM has been widely accepted and applied in a variety of settings due to its parsimony and explanatory power (Calantone, Yalcinkaya & Griffith, 2005, p. 155) and has formed the basis by means of which one can examine the acceptance of e-learning by academics and educators (e.g. Thang, Murugaiah, Lee, Azman, Tan & Lee, 2010;Tarcan, Varol & Toker, 2010;Birch & Burnett, 2009;Debuse, Lawley & Shibl, 2008;Swan, 2009) and students (e.g. Park, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…TAM has been widely accepted and applied in a variety of settings due to its parsimony and explanatory power (Calantone, Yalcinkaya & Griffith, 2005, p. 155) and has formed the basis by means of which one can examine the acceptance of e-learning by academics and educators (e.g. Thang, Murugaiah, Lee, Azman, Tan & Lee, 2010;Tarcan, Varol & Toker, 2010;Birch & Burnett, 2009;Debuse, Lawley & Shibl, 2008;Swan, 2009) and students (e.g. Park, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While the participating teachers and schools indicated enthusiasm for the potential of the model and welcomed the opportunity to create interschool communities of practice, the preliminary findings unfortunately generally revealed that the desired communities of practice (CoPs) as envisioned were not established. Thang et al (2010b) examined the reasons for this outcome from the perspectives of Brinkerhoff's framework (2006).…”
Section: Findings From the Preliminary Studymentioning
confidence: 99%
“…The four barriers discussed by Thang et al (2010b) in their research findings were: 1) resources; 2) institutional and administrative barriers; 3) institutional barriers relating to training and experience; and 4) barriers related to teachers' attitudes and fear. Each of the four barriers mentioned above are further elaborated below.…”
Section: Findings From the Preliminary Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, various studies in Malaysia have revealed that there is a strong preference for digital resources among teachers, and this might lead to digital libraries being accepted favourably by this educational community. Although research provided empirical evidence that Malaysian teachers have high positive attitudes towards web technology and have moderate levels of ICT competence (Bee Theng and Chia Hua, 2008), teachers are relatively slow to use digital resources in the teachinglearning process and not ready to adopt online tools such as blogs and discussion forums into the classrooms (Thang et al, 2010). The actual usage of computer (AUC) and Internet for classroom purposes remains moderate although training has been given (Kumar et al, 2008).…”
Section: Background and Context Of Inquirymentioning
confidence: 99%